DEVELOPMENT OF ALTERNATIVE FEED BASED ON SILAGE METHODS AND UTILIZATION OF GOAT MANURE AS ORGANIC FERTILIZER USING SIMPLE PROCESSING METHODS IN THE KUBE SEJAHTERA X BINANGUN 005 FARMER GROUP, SIDOHARJO VILLAGE, SAMIGALUH SUB-DISTRICT, KULON PROGO DISTRICT - Prastowo, Joko; Nugraheni, Yudhi Ratna; Ariyadi, Bambang; Pastawan, Viagian; Awaludin, Aan (Jurusan Peternakan Politeknik Pertanian Negeri Kupang, 2023)
The COVID-19 pandemic and the emergence of Foot and Mouth Disease (FMD) outbreaks have weakened the economy, including the goat farming subsector. The decrease in demand for goats in the livestock market is the most dominant impact. Presently, farmers are no longer thinking about profits but how to maintain their farms. Transferring knowledge about alternative feed by utilizing local resources and processing organic fertilizer from goat manure is one strategy to reduce maintenance costs and increase the selling value of goat manure with the optimism of becoming an additional source of income for farmer groups. The development of alternative feed using the silage method and goat manure processing is carried out with simple fermentation-based processing. Community service has been carried out with a counseling method accompanied by interactive discussions followed by self-practice with assistance. Evaluation of community service activities has been carried out by looking at and assessing the physical standard parameters of the products produced by farmers, consisting of the quality of silage and organic fertilizer. The results of this community service, member farmers from the KUBE Sejahtera X Binangun 005 farmer group were able to understand and successfully improve their skills in making alternative feed based on local resources using the silage method and making organic fertilizer with the main ingredient of goat manure.